Penerapan model pembelajaran discovery learning untuk meningkatkan keterampilan berpikir kritis pada pembelajaran ipas kelas iv sekolah dasar - Viastuti, Regita; Poerwanti, Jenny Indrastoeti Siti; Chumdari, Chumdari (Universitas Sebelas Maret, 2024)
The objectives of this study are: (1) To describe the learning process using the Discovery Learning model in improving critical thinking skills in science learning for Class IV of SD Negeri Kemasan 1, (2) To improve students' critical thinking skills using the Discovery Learning model in science learning for Class IV of SD Negeri Kemasan 1. This study is a collaborative Classroom Action Research (CAR) carried out in two cycles, each cycle consisting of two meetings in each cycle there are research stages, namely planning, implementation, observation, and reflection. The subjects of this study are 28 fourth grade students. The data used were qualitative data, namely the application of the Discovery Learning model and quantitative data, namely the critical thinking skills test in science lessons. Data collection techniques used observation, interviews, and tests. Data validity used triangulation techniques and sources. The Miles and Huberman model is used for data analysis. The result shows that critical thinking skills in pre-action reached an average of 53.821 with classical completeness of 7%. Cycle 1 reached an average of 68.357 with classical completeness of 54%. Cycle 2 obtained an average of 89.321 and classical completeness of 96%. Based on these data, it can be concluded that learning process that uses the steps of the Discovery Learning model is used by researchers to improve critical thinking skills in the Science subject with several steps, namely: (a) Stimulation, (b) Problem statement, (c) Data collection, (d) Data processing, (e) Verification, (f) Generalization. The application of the Discovery Learning model with the steps that have been explained can be carried out well to improve critical thinking skills in science in grade IV students of SD Negeri Kemasan 1 Surakarta in the 2023/2024 academic year and has achieved the targets that have been set.